PENGARUH PEMBERIAN JENIS SUMBER SERAT HIJAUAN TERHADAP KUALITAS SUSU KAMBING PERANAKAN ETAWA - Retno Iswarin Pujaningsih (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2017)
In general, goat milk production is strongly influenced by the quality of feed given. This study aims to evaluate the type of forage fiber feed source that has an effect on quality of ettawah goat milk. The material used is 12 lactation crossbreed ettawah goat month 3rd. Feed given is concentrate and source of fiber (Pennisetum purpureum grass, Albizia chinensis leaves, Zea mays straw). The consumption of dry matter, milk production and milk fat content were observed as parameters. The results show that the combination of concentrate with Zea mays straw can increase milk fat content up to 0.9%. Milk production was not significantly different in each treatment. It was concluded that the combination of concentrate and Zea mays straw was recommended to increase the milk fat content of crossbreed ettawah goat.